2021
DOI: 10.3390/ani11113119
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Impact of the Projected Ocean Acidification on Fish Survival, Health, Growth, and Meat Quality; Black Sea Bream (Acanthopagrus schlegelii), Physiological and Histological Studies

Abstract: Acidification (OA), a global threat to the world’s oceans, is projected to significantly grow if CO2 continues to be emitted into the atmosphere at high levels. This will result in a slight decrease in pH. Since the latter is a logarithmic scale of acidity, the higher acidic seawater is expected to have a tremendous impact on marine living resources in the long-term. An 8-week laboratory experiment was designed to assess the impact of the projected pH in 2100 and beyond on fish survival, health, growth, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Therefore, these decreases in BChE levels under OA conditions could explain the endocrine source of the increase in food intake observed by Tegomo et al. ( 337 ) in black sea bream.…”
Section: Effects Of Global Climate Change Factors On Growth and Feedi...mentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, these decreases in BChE levels under OA conditions could explain the endocrine source of the increase in food intake observed by Tegomo et al. ( 337 ) in black sea bream.…”
Section: Effects Of Global Climate Change Factors On Growth and Feedi...mentioning
confidence: 77%
“…An interesting case study that related growth with food intake was carried out in black sea bream by Tegomo et al. ( 337 ). Although the authors did not analyze the endocrine response of the growth axis, they observed that under two projected scenarios of OA, with pH values of 7.80-pCO 2 = 749.12 ± 27.03 and 7.40-pCO 2 = 321.37 ± 11.48 μatm, the growth, feeding efficiency, protein efficiency ratio, and crude protein content were significantly decreased in juveniles.…”
Section: Effects Of Global Climate Change Factors On Growth and Feedi...mentioning
confidence: 99%
“…Gills of marine and freshwater fish exhibited hypertrophy when exposed to acidification and elevated CO 2 at 25,000 μatm for 56 days in juvenile Turbot Scophthalmus maximus (Hermann et al 2019); at 1010 μatm for 120 days in juvenile hybrid grouper (Brown-marbled Grouper Epinephelus fuscoguttatus × Giant Grouper E. lanceolatus; Noor et al 2019); and at 2300 μatm for 14 days in adult Zebrafish Danio rerio (Thomas and Achiraman 2021). Additionally, aneurysms (Tegomo et al 2021) and necrosis (Thomas and Achiraman 2021) have also been observed. The liver is another commonly sampled tissue because it is the major organ responsible for supplying energy to the body (Bruslé and Anadson 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Gills are commonly sampled in ocean acidification studies as they are vital for ion regulation and gas exchange. For example, studies observing the gills of fish exposed to acidification saw hypertrophy under 2500 µatm for 56 days, 1010 µatm for 120 days, and 2300 µatm for 14 days (Hermann et al, 2019;Noor et al, 2019;Thomas and Achiraman, 2021), aneurysms (Tegomo et al, 2021), and even necrosis of the tissue (Thomas and Achiraman, 2021). Another major tissue that is commonly looked at when conducting histological examinations is the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Acidification has been shown to cause severe liver damage (Frommel et al, 2012;Tegomo et al, 2021) and failure in protein synthesis within marine fishes (Dickinson et al, 2012), but has yet to be described in a freshwater fish.…”
Section: Introductionmentioning
confidence: 99%